Resveratrol inhibits KSHV reactivation by lowering the levels of cellular Egr-1 - Dyson, Ossie F.; Walker, Lia R.; Whitehouse, Adrian; Cook, Paul P.; Akula, Shaw M. (My University, 2012)
In the field of herpesvirus research, the exact molecular mechanism by which such viruses reactivate from latency remains elusive. Kaposi's sarcoma-associated herpesvirus (KSHV) primarily exists in a latent state, while only 1-3% of cells support lytic infection at any specific time. KSHV reactivation from latency is an exceedingly intricate process mediated by the integration of viral and cellular factors. Previously, our lab has described early growth response-1 (Egr-1) as an essential component for the KSHV reactivation process via its ability to mediate transcription of KSHV ORF50, the gene encoding for replication and transcription activator (RTA), a viral component known to control the switch from latent to lytic infection. In here, electrophoretic mobility shift assays (EMSA) and chromatin immunoprecipitation (ChIP) experiments revealed that Egr-1 binds KSHV ORF50 promoter (ORF50P) in at least two different GC-rich binding domains. Expression profiles of cellular egr-1 and KSHV-encoded ORF50 follow a similar pattern during de novo KSHV infection. Over-expressing Egr-1, a signaling component downstream of Raf>MEK>ERK1/2, in KSHV-infected cells activates KSHV lytic replication. Through performing more physiologically relevant experiments, we analyzed the effect of a dietary supplement containing resveratrol on KSHV-infected cells. Our results, for the first time, demonstrate resveratrol to act in lowering ERK1/2 activity and expression of Egr-1 in KSHV-infected cells, resulting in the suppression of virus reactivation from latency. Taken together, these findings will undoubtedly contribute to future studies on not only combating KSHV related disease conditions, but also on other herpesviruses-induced pathogenesis.